Do microplastics play a role in the pathogenesis of neurodegenerative diseases? Shared pathophysiological pathways for Alzheimer’s and Parkinson’s disease - Alexander Chi Wang Siu; Keshav Raj Paudel; Gurjeet Singh; Gaurav Gupta; Sachin Kumar Singh; Dinesh Kumar Chellappan; Gabriele De Rubis; Suhrud Pathak; Brian Gregory George Oliver; Kamal Dua; Muralikrishnan Dhanasekaran (Molecular and Cellular Biochemistry, 2025)
The widespread presence of microplastics (MPs) in the environment has raised significant concerns about their potential impact on human health. As of 2023, the Ocean Conservancy estimates that adults may ingest up to 121,000 MPs annually. While the majority of these particles are cleared from the body, a small fraction can persist, as MPs are non-biodegradable and resist breakdown, posing long-term health risks that remain poorly understood. This review explores the emerging link between MP exposure and the development of neurodegenerative diseases, particularly Alzheimer’s disease (AD) and Parkinson’s disease [1]. MPs appear capable of triggering neurotoxic pathways, including activation of resident immune cells in the brain, oxidative stress, blood–brain barrier (BBB) disruption, mitochondrial dysfunction, and neuronal damage, which may contribute to neuroinflammation and disease progression. Specifically, six MP-related mechanistic pathways associated with AD were identified: BBB disruption, chronic inflammation, oxidative stress and ROS generation, mitochondrial dysfunction, impaired autophagy and proteostasis, and epigenetic alterations. Similarly, six pathways were implicated in PD: BBB disruption, oxidative stress in dopaminergic neurons, mitochondrial dysfunction, microglial-driven neuroinflammation, α-synuclein aggregation, and gut–brain axis [2] disruption. Ultimately, our findings underscore the urgent need for further research into the neurological consequences of chronic MP exposure in humans and highlight the importance of strengthening global policies to curb plastic pollution and mitigate its long-term health risks.